Clinical and pathological implications of GSTM1 and GSTT1 gene deletions in sporadic breast cancer - Cassio Cardoso Filho; Gustavo Lourenço; Julia Yoriko Shinzato; Luiz Carlos Zeferino; Fernando Ferreira Costa; Carmen Silvia Passos Lima; Maria Salete Costa Gurgel (Frontiers Media S.A., 2011)
There is a lack of consensus about the influence of GST M1/T1 gene deletions (DEL) on sporadic breast cancer (SBC). To evaluate the occurrence of DEL in 177 SBC cases and in 169 controls, and compare clinical and biological characteristics. A lower frequency of GSTM1 DEL was observed in mulatto women, OR=0.48 (0.24-0.98). The risk of nuclear grade 3 tumors (GN3) was lower in patients with GSTT1 DEL, OR=0.37 (0.15-0.90). DEL of at least one gene (ALOG) was associated with women who had not breastfed, OR=0.41 (0.19-0.88), and with negative hormone receptor, HR-, ORadj=2.25 (1.03-4.90). Both genes deleted (BGD) was associated with non-classic invasive ductal carcinoma (NCDC), ORadj=12.09 (1.03-142.03). Mulatto women with SBC had a lower frequency of GSTM1 DEL, while tumors differentiated were related to GSTT1 DEL. HRtumors were related with DEL ALOG, and the BGD was associated with a greater risk of NCDC.